Growth in a Differentiated Oligopoly with Product Innovation - Luca Lambertini; Roberto Cellini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
We present a two-sector model where oligopolistic firms sell differentiated products. New products are introduced over time through formal R&D activity. Market competition takes place either a la Cournot or a la Bertrand. We show that tougher competition associated wit price-setting behavior does not entail a larger social welfare as long as it requires more effort for the production of the final goods.
Keywords: 330